Analysis of parameters affecting the performance of optical camera communication system - Nguyễn Duy Thông; Phạm Văn Khoa (Journal of Technical Education Science, 2021)
Optical camera communication (OCC) system is a scheme that uses LED and an image sensor (IS) to transmit and receive signal. However, the applications of OCC are still limited due to low data rate and short transmission distance. To further enhance the system performance, this study will evaluate the parameters that affect the system performance. The experimental and analytical results show that flickering and inter-frame gap (IFG) significantly reduce the data rate of the system. Blooming phenomenon also causes the IFG to become wider, and affects the transmission distance. The light intensity of the transmitter needs to be considered to conform the lighting system and avoid the saturation problem. In this paper, the performent of system is compared with data rate of 1.8 kbps and 3.6 kbps. The experimental results show that there is a trade-off between data rate and transmission distance. Therefore, depending on the specific application, the parameters of the image sensor should be considered carefully and appropriately.